PENGEMBANGAN MULTIMEDIA INTERAKTIF MENGGUNAKAN APLIKASI SMART APPS CREATOR PADA MATERI SISTEM PENCERNAAN MANUSIA - Rachma Safitri, Nur; Yuyun Elizabeth Patras; Ade Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to address the lack of engagement in learning activities in a specific elementary school classroom by developing interactive learning media. The focus of this study is to create an application-based interactive multimedia on the topic of the human digestive system for fifth grade students. The research follows the R&D approach with the ADDIE model, involving analysis, design, development, implementation, and evaluation stages. Data was collected through observations, interviews, questionnaires, and documentation, and analyzed qualitatively and quantitatively. The developed media was validated by experts in the field, and a trial was conducted with 21 students. The results showed high percentages of validation and trial success, media validation that have been carried out obtained a percentage of 96%, 100% language validation, and 85% material validation, with 93% overall average, indicating that the developed interactive multimedia is highly suitable for learning activities and considered "very worthy" by the participants. Thus, it can be concluded that the smart apps creator application is an effective tool for engaging students in learning about the human digestive system.